2021
DOI: 10.1371/journal.pone.0261196
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome of Hordeum brevisubulatum: Genome organization, synonymous codon usage, phylogenetic relationships, and comparative structure analysis

Abstract: Background Hordeum brevisubulatum, known as fine perennial forage, is used for soil salinity improvement in northern China. Chloroplast (cp) genome is an ideal model for assessing its genome evolution and the phylogenetic relationships. We de novo sequenced and analyzed the cp genome of H. brevisubulatum, providing a fundamental reference for further studies in genetics and molecular breeding. Results The cp genome of H. brevisubulatum was 137,155 bp in length with a typical quadripartite structure. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…In addition, the fragment from 8,966 to 52,067 bp was in inverse order in the LSC region, which was different from the reported cp genome of K. obovata (Chen et al, 2019;Yang et al, 2019). This inversion has been previously reported in other cp genomes (Wei et al, 2020;Cui et al, 2021;Kim & Cheon, 2021;Wang et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the fragment from 8,966 to 52,067 bp was in inverse order in the LSC region, which was different from the reported cp genome of K. obovata (Chen et al, 2019;Yang et al, 2019). This inversion has been previously reported in other cp genomes (Wei et al, 2020;Cui et al, 2021;Kim & Cheon, 2021;Wang et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we compared the cp genome structure of ve Clematis species using mVISTA (using Clematis fruticosa as a reference) and found that the non-coding region was more prone to mutations than the coding region. Furthermore, the variation in the SC region was higher than that in the IR region, which is similar to the results of previous plant studies [25,51,53]. psbA-atpA, atpI-rpoC2, rpoB-psbD, psbE-petG, clpP, and rpoC2 were the most highly variable regions detected in C. nannophylla.…”
Section: Codon Usage Bias In the Cp Genome Of C Nannophyllasupporting
confidence: 90%
“…The expansion and contraction of the IR region boundaries are common evolutionary events in most angiosperms, which may lead to variations in cp genome length, gene replication or reduction, and the origin of pseudogenes [47,48]. This study found that IR expansion and contraction of C. nannophylla showed great similarity with other plants of Clematis, and these regional genotypes and distribution locations are similar [25]. However, only minor differences were observed near the IRb/SSC boundaries.…”
Section: Codon Usage Bias In the Cp Genome Of C Nannophyllamentioning
confidence: 74%
See 1 more Smart Citation
“…The chloroplast genome is a typical double-stranded circular multi-copy DNA molecule in cells. Plant chloroplast (cp) genomes are very conserved and can be divided into four segments, namely two inverted repeat (IRa and IRb) regions, a large single copy (LSC) region, and a small single copy (SSC) region separating IR regions (Wicke et al, 2011;Cui et al, 2021). The expansion or contraction of the IR regions often results in the variation in length of the chloroplast genome (Chung et al, 2006).…”
Section: Introductionmentioning
confidence: 99%